2022
DOI: 10.17352/2455-2283.000111
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with response to highly active antiretroviral therapy after 24 months of administration to HIV, HIV/HBV and HCV patients in Kumba Health District, South West Region of Cameroon

Abstract: Hepatitis B (HBV) and C (HCV) are two other forms of infections for which co-infection in HIV has been associated with alteration of the immune response, increased risk of progression to liver diseases, and increased risk of hepatotoxicity associated with antiretroviral therapy. This study aimed to establish the prevalence of hepatitis B surface antigen (HBsAg) and hepatitis C antibody (HCVAb) among HIV patients, evaluate response to treatment between the different categories and identify the possible risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…HCVAb seroprevalence in Cameroon varies across regions and tribes within the same country. While some studies reported high HCVAb carriage: in the southern 12% [35], in the western6.3% [36], numerous studies on the contrary revealed a relative much lower prevalence: 2.2% anti-HCV in the Northern [37], 0.6% in the eastern [38], 0.4% in the western [39], 4.8% in the Littoral Region [40], 1.44% in the center region [41]. Equally, various burden of anti-HCV antibodies have also been reported in community settings worldwide: 0.77% in Romania [42], 1.02% in Sudan [43], 1.2% in Madagascar [44], 2.4%in Iraq [45], 3.6% in India [46], 19.80% in Cairo [47].…”
Section: Liver Impairment According To Hepatitis C Antibodies Carriag...mentioning
confidence: 98%
“…HCVAb seroprevalence in Cameroon varies across regions and tribes within the same country. While some studies reported high HCVAb carriage: in the southern 12% [35], in the western6.3% [36], numerous studies on the contrary revealed a relative much lower prevalence: 2.2% anti-HCV in the Northern [37], 0.6% in the eastern [38], 0.4% in the western [39], 4.8% in the Littoral Region [40], 1.44% in the center region [41]. Equally, various burden of anti-HCV antibodies have also been reported in community settings worldwide: 0.77% in Romania [42], 1.02% in Sudan [43], 1.2% in Madagascar [44], 2.4%in Iraq [45], 3.6% in India [46], 19.80% in Cairo [47].…”
Section: Liver Impairment According To Hepatitis C Antibodies Carriag...mentioning
confidence: 98%